Eosin B as a Novel Antimalarial Agent for Drug-Resistant Plasmodium falciparum - Massimine, Kristen M. (American Society for Microbiology, 2006)
4′,5′-Dibromo-2′,7′-dinitrofluorescein, a red dye commonly referred to as eosin B, inhibits Toxoplasma gondii in both enzymatic and cell culture studies with a 50% inhibitory concentration (IC(50)) of 180 μM. As a non-active-site inhibitor of the bifunctional T. gondii dihydrofolate reductase-thymidylate synthase (DHFR-TS), eosin B offers a novel mechanism for inhibition of the parasitic folate biosynthesis pathway. In the present study, eosin B was further evaluated as a potential antiparasitic compound through in vitro and cell culture testing of its effects on Plasmodium falciparum. Our data revealed that eosin B is a highly selective, potent inhibitor of a variety of drug-resistant malarial strains, with an average IC(50) of 124 nM. Furthermore, there is no indication of cross-resistance with other clinically utilized compounds, suggesting that eosin B is acting via a novel mechanism. The antimalarial mode of action appears to be multifaceted and includes extensive damage to membranes, the alteration of intracellular organelles, and enzymatic inhibition not only of DHFR-TS but also of glutathione reductase and thioredoxin reductase. In addition, preliminary studies suggest that eosin B is also acting as a redox cycling compound. Overall, our data suggest that eosin B is an effective lead compound for the development of new, more effective antimalarial drugs.